Question
upstudy study bank question image url

9. Determine the value of each expression: \( \begin{array}{llll}\text { (a) } 27^{\frac{1}{3}} & \text { (b) } 32^{\frac{3}{5}} & \text { (c) } 49^{-\frac{1}{2}} & \text { (d) }\left(\frac{16}{81}\right)^{-\frac{3}{4}}\end{array} \)

Ask by Dawson Johnston. in Curaçao
Jan 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The answers are: - (a) 3 - (b) 8 - (c) 1/7 - (d) 27/8

Solution

Let's evaluate each expression step by step: ### (a) \( 27^{\frac{1}{3}} \) This represents the cube root of 27. - **Calculation:** \[ 27 = 3^3 \implies 27^{\frac{1}{3}} = (3^3)^{\frac{1}{3}} = 3^{3 \times \frac{1}{3}} = 3^1 = 3 \] - **Answer:** \( 3 \) --- ### (b) \( 32^{\frac{3}{5}} \) This can be interpreted as the 5th root of 32 raised to the 3rd power. - **Express 32 as a power of 2:** \[ 32 = 2^5 \] - **Calculation:** \[ 32^{\frac{3}{5}} = (2^5)^{\frac{3}{5}} = 2^{5 \times \frac{3}{5}} = 2^3 = 8 \] - **Answer:** \( 8 \) --- ### (c) \( 49^{-\frac{1}{2}} \) A negative exponent indicates a reciprocal, and the exponent \(\frac{1}{2}\) represents a square root. - **Express 49 as a power of 7:** \[ 49 = 7^2 \] - **Calculation:** \[ 49^{-\frac{1}{2}} = (7^2)^{-\frac{1}{2}} = 7^{2 \times -\frac{1}{2}} = 7^{-1} = \frac{1}{7} \] - **Answer:** \( \frac{1}{7} \) --- ### (d) \( \left(\frac{16}{81}\right)^{-\frac{3}{4}} \) A negative exponent indicates taking the reciprocal, and the exponent \(\frac{3}{4}\) involves roots and powers. - **Express 16 and 81 as powers:** \[ 16 = 2^4 \quad \text{and} \quad 81 = 3^4 \] - **Rewrite the expression:** \[ \left(\frac{16}{81}\right)^{-\frac{3}{4}} = \left(\frac{2^4}{3^4}\right)^{-\frac{3}{4}} = \left(\frac{2}{3}\right)^{4 \times -\frac{3}{4}} = \left(\frac{2}{3}\right)^{-3} = \left(\frac{3}{2}\right)^3 = \frac{27}{8} \] - **Answer:** \( \frac{27}{8} \) --- ### **Summary of Answers:** - **(a)** \( 3 \) - **(b)** \( 8 \) - **(c)** \( \frac{1}{7} \) - **(d)** \( \frac{27}{8} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Let's evaluate each expression step by step: (a) \( 27^{\frac{1}{3}} \): The cube root of 27 is 3, because \( 3^3 = 27 \). (b) \( 32^{\frac{3}{5}} \): First, find \( 32^{\frac{1}{5}} \) which is the fifth root of 32, equal to 2 (since \( 2^5 = 32 \)). Then raise it to the power of 3: \( 2^3 = 8 \). So, \( 32^{\frac{3}{5}} = 8 \). (c) \( 49^{-\frac{1}{2}} \): The negative exponent indicates a reciprocal, while the \( \frac{1}{2} \) exponent means we need to take the square root. The square root of 49 is 7, and the negative exponent means we take the reciprocal, giving us \( \frac{1}{7} \). (d) \( \left(\frac{16}{81}\right)^{-\frac{3}{4}} \): First, take the reciprocal due to the negative exponent: \( \left(\frac{81}{16}\right)^{\frac{3}{4}} \). Then compute \( \frac{81}{16} \), which will yield \( \sqrt[4]{\frac{81^3}{16^3}} \). The fourth root of 81 is 3, raised to the power of 3 gives us 27. The fourth root of 16 is 2, raised to the power of 3 gives us 8. Thus, \( \left(\frac{16}{81}\right)^{-\frac{3}{4}} = \frac{27}{8} \). In summary: (a) \( 27^{\frac{1}{3}} = 3 \) (b) \( 32^{\frac{3}{5}} = 8 \) (c) \( 49^{-\frac{1}{2}} = \frac{1}{7} \) (d) \( \left(\frac{16}{81}\right)^{-\frac{3}{4}} = \frac{27}{8} \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy